ANALISIS KEPUASAN WISATAWAN NUSANTARA BERBELANJA DI KRISNA OLEH-OLEH KHAS BALI - Nanda Anggriawan, Yosia; Wijaya, NMS.; Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 1 (2020): Jurnal IPTA (July 2020)DO - 10.24843/IPTA.2020.v08.i01.p18, 2020)
The purpose of this study was to find out the satisfaction of shopping for domestic tourist at Krisna Oleh-Oleh Khas Bali. Based on statistical data, domestic tourists who choose shopping tourism activities and allocation of expenditure to buy souvenirs while on vacation to Bali ranks in the second place. Data were collected by observation, questionnaire, documentation, and literature study using accidental & purposive sampling techniques with a total of 100 respondents. To analyze data, the data analysis techniques used are validity, reliability, expectation and satisfaction. Measurements are made with three factors that influence the satisfaction of the tourist shopping of the domestic tourist in Krisna Oleh-Oleh Khas Bali. The three factors are in-store, out-store, and marketing mix and the average value of expectation is 4.14 which is in the important category, then the average value of the performance level of 3.81 is in the good category. From the results of the level of expectation and level of performance, the suitability level of 92.4% is categorized as less satisfied, which means that the domestic tourists who shop at Krisna Oleh-Oleh Khas Bali feel less satisfied. There are 7 indicators that are a priority in Krisna Oleh-Oleh Khas Bali to be improved, the indicators are the in-store scent, food court cleanliness, food court comfort, waiting area comfort, noise levels, special offers or discounts, and prices. The advice that can be given to Krisna Oleh-Oleh Khas Bali is to improve the performance that is deemed lacking like the priority already mentioned.